2023
DOI: 10.1109/tnsre.2022.3222095
|View full text |Cite
|
Sign up to set email alerts
|

Channel Increment Strategy-Based 1D Convolutional Neural Networks for Seizure Prediction Using Intracranial EEG

Abstract: The application of intracranial electroencephalogram (iEEG) to predict seizures remains challenging. Although channel selection has been utilized in seizure prediction and detection studies, most of them focus on the combination with conventional machine learning methods. Thus, channel selection combined with deep learning methods can be further analyzed in the field of seizure prediction. Given this, in this work, a novel iEEG-based deep learning method of One-Dimensional Convolutional Neural Networks (1D-CNN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Hence, 2D-CNN and 3D-CNN will not be suitable to implement low-power/low-memory devices. The 1D-CNN can achieve excellent performance in several applications [21], [40]. Our main aim is to implement a seizure prediction device which will be low-cost hardware.…”
Section: B Features Extraction and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, 2D-CNN and 3D-CNN will not be suitable to implement low-power/low-memory devices. The 1D-CNN can achieve excellent performance in several applications [21], [40]. Our main aim is to implement a seizure prediction device which will be low-cost hardware.…”
Section: B Features Extraction and Classificationmentioning
confidence: 99%
“…Hence, most of the researchers used deep learning techniques, which were used to extract the most relevant features from the EEG signals for the classification of pre-ictal and inter-ictal states to predict seizures in advance. The most commonly used deep learning techniques are Convolution neural networks [19], [20], [21], LSTM [22], [23], [24], DenseNet [24], [25], Self-Organizing Maps [26], and Long-term recurrent convolutional networks [27]. It was found that the use of deep learning techniques provided better accuracy for seizure prediction.…”
Section: Introductionmentioning
confidence: 99%